Use of ethylene-vinyl acetate in early childhood education: bibliometric overview and environmental implications - Aguiar Lima, Vanessa; Aguiar de Lima da Costa, Ana Cristina; Rodrigues da Cunha Neto, Antonio; dos Santos Ambrósio, Alexandra; da Glória Teixeira Silveira, Laís; Zanateli, Carlos Henrique; Messias Lima, Thais Fátima; Mikaela Rabelo, Valquíria; Régis Santos, Breno (Sigmae, 2025)
Ethylene-vinyl acetate (EVA) is a copolymer whose properties can be modified by varying the amount of vinyl acetate. Among its applications, the creation of educational play materials stands out; however, improper disposal of EVA poses an environmental risk due to its potential as a pollutant. Thus, this study aimed to analyze, through bibliometric methods, the scientific discourse related to EVA and correlate the findings with a case study evaluating its use in an educational center. Initially, a bibliometric analysis was conducted using data from the last ten years, highlighting the predominance of publications in polymer and materials science, while few studies focus on the environmental and educational impacts of EVA. A case study conducted at a Municipal Center for Early Childhood Education, using Principal Component Analysis to reduce dimensionality and identify latent patterns in the data, followed by K-Means clustering for group segmentation, revealed that although many educators use EVA in educational activities, there is little awareness of its environmental impacts and inadequate disposal practices. Bibliometric analysis revealed EVA research predominantly focuses on materials science, with minimal attention to environmental and educational impacts. A case study identified three educator profiles: Cluster 1 (60%) showed high environmental awareness but inconsistent sustainable practices; Cluster 0 (18%) demonstrated high EVA dependence with low sustainability awareness; Cluster 2 (22%) exhibited moderate awareness but limited practical alternatives. It is concluded that a transition to more sustainable educational practices requires a concerted effort among educators, institutions, and policymakers, aligned with the Sustainable Development Goals.